Development of E-Comic Based on Problem Based Learning in Human Influence on Ecosystems Topic to Increase Students Environmental Literacy - Salsabila Rofifah; Dian Nugraheni; Indra Fardhani; Yayuk Mulyati; Himawan Ganjar Prabowo (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Environmental literacy is one of the important skills of the 21st century that needs to be developed along with increasingly complex global environmental changes, especially related to the issue of plastic waste which is a real problem in the school environment. However, learning at one of the junior high schools in Tulungagung is not optimal in fostering environmental awareness and the media used is not varied enough. The purpose of this study is to produce a PBL-based e-comic that is feasible, practical, and effective in improving students' environmental literacy on the material of human influence on the ecosystem. This study uses the ADDIE development model. The results of the media validity test of 89.79% and material of 90.00% were classified as very valid, and the assessment instruments used were valid and reliable. The practicality test by teachers and students obtained a percentage of 91.30% classified as very practical. The effectiveness test showed that there was an increase in environmental literacy between before the application of media (pretest) and after the application of media (posttest) with an average n-gain value of all environmental literacy indicators of 0.33 including the moderate category. The findings of this study indicate that e-comic based on Problem Based Learning are feasible to use, practical, and able to improve students' environmental literacy